Beyond the laboratory: the bank vole (Clethrionomys glareolus) as a novel model organism in biological research - Górska, Joanna; Kotlík, Petr; Henttonen, Heikki; Bajer, Anna; Behnke, Jerzy M.; Radwan, Jacek; Koteja, Paweł; Mappes, Tapio; Grzybek, Maciej (BioMed Central, 2025)
Rodents constitute a significant proportion of mammalian diversity, with their adaptability and wide distribution making them indispensable study organisms across various biological disciplines. While the laboratory mouse remains a predominant model rodent, the bank vole (Clethrionomys glareolus) offers a unique perspective as a wild rodent within the large subfamily Arvicolinae. Recognized for its relevance to studynatural ecology, the bank vole provides insights into complex ecological interactions, evolutionary adaptations, and disease dynamics. Despite recent recognition of its importance in specific research areas, there is a lack of a comprehensive and up-to-date exploration of its role as a model organism. This review addresses this gap by offering a holistic examination of the bank vole’s applications in ecology, evolution, biogeography, disease dynamics, and host–pathogen interactions. We emphasize novel insights into genetic variation, adaptation to climate change, population dynamics, experimental evolution, host-parasite co-evolution, and disease dynamics studies. By consolidating diverse research findings, this review provides a unique and comprehensive perspective on the bank vole’s contributions to understanding ecology and evolution, underscoring its importance as a model organism in shaping future biological research.
Keywords: rodents; bank vole; Myodes glareolus; model organism; genetics; ecology